2007
DOI: 10.1074/mcp.m600310-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Distorted Relation between mRNA Copy Number and Corresponding Major Histocompatibility Complex Ligand Density on the Cell Surface

Abstract: The major histocompatibility complex (MHC) presents peptides derived from degraded cellular proteins to Tcells and is thus crucial for triggering specific immune responses against viral infections or cancer. Up to now, there has been no evidence for a correlation between levels of mRNA (the "transcriptome") and the density of MHC-peptide complexes (the "MHC ligandome") on cells. Because such dependences are of intrinsic importance for the detailed understanding of translation efficiency and protein turnover an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
114
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 116 publications
(126 citation statements)
references
References 41 publications
11
114
0
Order By: Relevance
“…This suggests that the relevant antigen-processing compartment translates multiple mRNAs into DRiPs whose peptides compete for class I binding. Although our findings are limited to VV-derived peptides, it is likely that they extend to peptides derived from cellular proteins, because the findings provide an explanation for CD8 + T cell recognition of peptides encoded by low abundance or unusual mRNAs, as well as for the poor correlation between the immunopeptidome and the transcriptome or proteome (14)(15)(16). Consistent with the proposal that immunoribosomes translate nascent RNA (4), Gu et al (17) recently reported that truncated RNA generated via RNAi are an efficient source of antigenic peptides.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the relevant antigen-processing compartment translates multiple mRNAs into DRiPs whose peptides compete for class I binding. Although our findings are limited to VV-derived peptides, it is likely that they extend to peptides derived from cellular proteins, because the findings provide an explanation for CD8 + T cell recognition of peptides encoded by low abundance or unusual mRNAs, as well as for the poor correlation between the immunopeptidome and the transcriptome or proteome (14)(15)(16). Consistent with the proposal that immunoribosomes translate nascent RNA (4), Gu et al (17) recently reported that truncated RNA generated via RNAi are an efficient source of antigenic peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Interpretation of MS/MS fragmentation spectra was carried out manually using MassLynx 4.0 software 47 . For manual peptide identification, sequence tag searches were done using Mascot 2.0 software (peptide and MS/MS tolerance, 0.2 Da; National Center for Biotechnology Information non-redundant (NCBInr) database updated monthly and restricted for search to human entries), and relevant hits were assessed manually and not by evaluation of the Mascot score.…”
Section: Methodsmentioning
confidence: 99%
“…This strategy is based on a technique recently established in our laboratory (36) to compare the repertoires of HLA ligands of tumor and healthy tissue (37,38). We found 15 viral peptides, of which 12 were presented by HLA-A*0201 and 3 by HLA-B*0702.…”
mentioning
confidence: 99%